2007
DOI: 10.1016/j.jmb.2006.12.005
|View full text |Cite
|
Sign up to set email alerts
|

A Tightly Packed Hydrophobic Cluster Directs the Formation of an Off-pathway Sub-millisecond Folding Intermediate in the α Subunit of Tryptophan Synthase, a TIM Barrel Protein

Abstract: Protein misfolding is now recognized as playing a crucial role in both normal and pathogenic folding reactions. An interesting example of misfolding at the earliest state of a natural folding reaction is provided by the alpha subunit of tryptophan synthase, a (β/α) 8 TIM barrel protein. The molecular basis for the formation of this off-pathway misfolded intermediate, I BP , and a subsequent on-pathway intermediate, I1, was probed by mutational analysis of 20 branched aliphatic side chains distributed throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 62 publications
6
95
0
Order By: Relevance
“…S2). Protein folding studies indicate that clusters of these three aliphatic amino acids form strong associations capable of directing folding pathways (25,26). The aliphatic patch at the C-domain dimer interface is consistent with the critical role of subunit association in the function of the Hsp90 and our observations that subunit dissociation does not appear to be required for essential Hsp90 function.…”
Section: Discussionsupporting
confidence: 85%
“…S2). Protein folding studies indicate that clusters of these three aliphatic amino acids form strong associations capable of directing folding pathways (25,26). The aliphatic patch at the C-domain dimer interface is consistent with the critical role of subunit association in the function of the Hsp90 and our observations that subunit dissociation does not appear to be required for essential Hsp90 function.…”
Section: Discussionsupporting
confidence: 85%
“…Hydrogen exchange experiments on the TIM barrel protein family have shown that clusters of isoleucine, leucine, and valine residues can accurately predict cores of stability (67) and early folding events (68,69). Using an in-house algorithm (see the Clusters of Branched Aliphatic Side Chains in Globular Proteins (BASiC) Web site) (70,71)), clusters of the branched aliphatic side chain residues in RRM1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Its conservation might reflect the (βα) n -repeat architecture of these barrels and, thereby, the opportunity for local and rapid folding reactions to forms of sufficient stability to be transiently populated during folding. As has been previously speculated, 51 this structure may not be able to propagate to the remainder of the sequence because it adopts a non-native local fold or because its edges adopt a non-native fold that enhances its interactions with solvent before the propagation reaction can occur.…”
Section: Why Are the On-and Off-pathway Intermediates For (βα) 8 Barrmentioning
confidence: 94%
“…In both cases, the protection patterns correlate with the presence of large hydrophobic clusters dominated by the branched aliphatic side chains from isoleucine, leucine and valine residues. 24,51 Thus, as the sequences of these (βα) 8 barrels evolved, the location of the structured regions defining the equilibrium intermediate moved with the location of the ILV-dominated hydrophobic clusters.…”
Section: Barrel Proteinsmentioning
confidence: 99%